Composite oxide film and preparation method thereof
By depositing modified silicone polymers on the surface of the anodized film, the problem that the anodized film is prone to corrosion in special environments is solved, and the wear resistance of the oxide layer is improved and the service life is extended.
Patent Information
- Application Number
- CN202411369637.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2025-01-17
AI Technical Summary
The anodic oxide film is easily damaged by physical or chemical actions during use, resulting in a degradation of performance, especially in special environments such as acid and alkali, high humidity, and high temperature.
Cathodic electrophoretic coating technology is used to deposit modified silicone polymers on the oxide layer to form a deposition layer with strong adhesion and hydrophobic properties, thus improving the wear resistance and service life of the oxide layer.
Through the protective effect of the deposited layer, the service life of the oxide layer is extended, the bonding force between the deposited layer and the surface of the metal workpiece is enhanced, the interaction between corrosive substances and the deposited layer is reduced, and the corrosion resistance of the metal workpiece is ensured when used in special environments.
Smart Images

Figure CN119320970A_ABST
Abstract
Description
[Technical field]
[0001] The present application relates to the field of anodizing technology, and in particular to a composite oxide film and a preparation method thereof. [Background technology]
[0002] Anodizing is a commonly used metal surface treatment technology. This technology will form a dense oxide film on the surface of the metal workpiece. This oxide film has good corrosion resistance, wear resistance, insulation and other characteristics.
[0003] After the oxide layer is prepared, it is easy to gradually lose its original properties due to physical or chemical effects. For example, during the use of the metal workpiece, the oxide layer is damaged by friction, collision and other reasons, causing the oxide layer to fall off, become thinner or scratched; or the oxide layer of the metal workpiece is exposed to special environments such as acid and alkali, high humidity and high temperature for a long time, and the oxide layer is corroded by moisture, acid, alkali and other substances, and the corrosion rate or aging process is accelerated, which leads to the destruction of the oxide layer. [Summary of the invention]
[0004] In view of this, the present application provides a composite oxide film and a preparation method thereof, which increases the service life of the oxide layer by depositing a deposition layer with strong adhesion and hydrophobic properties on the surface of the oxide layer.
[0005] In a first aspect, the present application provides a method for preparing a composite oxide film, the method for preparing the composite oxide film comprising the following steps:
[0006] Anodizing the surface of a metal workpiece to form an oxide layer;
[0007] The modified organic silicon polymer is deposited on the oxide layer by cathode electrophoretic coating technology to form a deposition layer, thereby obtaining a composite oxide film; wherein the modified organic silicon polymer contains a positively charged modified epoxy resin unit and a negatively charged hydrophobic fluorine-containing group.
[0008] In combination with the first aspect, the method further includes preparing the modified organic silicon polymer, wherein the preparation of the modified organic silicon polymer includes:
[0009] The organosilicon-modified epoxy acrylic resin is subjected to a ring-opening reaction with an amine ring-opening agent to obtain a ring-opening product; wherein the amine ring-opening agent comprises at least one of monoethanolamine, diethanolamine and triethanolamine;
[0010] The ring-opening product is subjected to acidification treatment to obtain the modified organic silicon high molecular polymer.
[0011] In combination with the first aspect, the method further includes preparing the organosilicon-modified epoxy acrylic resin, wherein the preparation of the organosilicon-modified epoxy acrylic resin includes:
[0012] The epoxy resin, hydroxyl chain extender, methacrylamide and modified silicone quantum dots are mixed in a preset mass ratio and then subjected to polymerization reaction to obtain the silicone-modified epoxy acrylic resin; wherein the preset mass ratio is (50-100): (2-30): (10-50): (1-10).
[0013] In combination with the first aspect, the hydroxy chain extender includes at least one of ethylene glycol ethyl ether, dimethylol propionic acid and dimethylol butyric acid.
[0014] In combination with the first aspect, the method further includes preparing the modified organic silicon quantum dots, wherein the preparing the organic silicon quantum dots includes:
[0015] Hydroxypropyl methacrylate and perfluorooctyltriethoxysilane are mixed in a preset mass ratio and reacted to obtain modified silicone quantum dots; wherein the preset mass ratio is (2-8): (1-3).
[0016] In combination with the first aspect, after anodizing the surface of the metal workpiece to form an oxide layer, the method further includes:
[0017] The oxide layer is etched with an etchant solution to form diffuse reflective microcracks.
[0018] In combination with the first aspect, the etching solution contains SO4 2- , the SO4 2- The concentration is 0.03mol / L~3mol / L.
[0019] In combination with the first aspect, the modified organic silicon polymer is deposited on the oxide layer using the cathode electrophoretic coating technology to form a deposition layer having at least one of the following characteristics:
[0020] (1) The reaction temperature is 25°C to 30°C;
[0021] (2) Voltage is 60V to 70V;
[0022] (3) The reaction time is 25s to 30s.
[0023] In a second aspect, the present application provides a composite oxide film, which includes an oxide layer and a deposition layer formed on the oxide layer, wherein the deposition layer includes a modified silicone polymer containing a positively charged modified epoxy resin unit and a negatively charged hydrophobic fluorine-containing group.
[0024] In combination with the second aspect, the oxide layer contains diffuse reflective microcracks, and the deposition layer is formed on the surface of the oxide layer and in the diffuse reflective cracks.
[0025] In combination with the second aspect, the composite oxide film has at least one of the following characteristics:
[0026] (1) The thickness of the composite oxide film is 10 μm to 30 μm;
[0027] (2) The pore size of the composite oxide film is 40 nm to 80 nm;
[0028] (3) The width of the diffuse reflection microcracks is 5 nm to 20 nm;
[0029] (4) The depth of the diffuse reflection microcracks is 30nm to 50nm;
[0030] (5) The thickness of the deposited layer is 5 μm to 20 μm;
[0031] (6) The L value of the composite oxide film is ≥90;
[0032] (7) The water contact angle of the composite oxide film is ≥130°.
[0033] By adopting the above technical solution, the present application has at least the following beneficial effects:
[0034] The preparation method of the composite oxide film provided in the present application adopts the cathode electrophoretic painting technology to deposit the modified organic silicon polymer on the oxide layer to form a deposition layer. The deposition layer attached to the oxide layer can provide protection, improve the wear resistance of the oxide layer, and extend the service life of the oxide layer. In addition, the deposition layer contains positively charged modified epoxy resin units, and the positive charge can enhance the bonding force between the deposition layer and the oxide layer on the surface of the negatively charged metal workpiece, prevent the deposition layer from falling off during use, and extend the protection time of the deposition layer on the oxide layer; at the same time, the deposition layer also contains negatively charged hydrophobic fluorine-containing groups, and the hydrophobicity of the fluorine-containing groups can significantly reduce the interaction between water molecules, acids, alkalis and other corrosive substances and the surface of the deposition layer, so that the metal workpiece can be used in special environments such as acid and alkali, high humidity, and high temperature.
Brief Description of the Drawings
[0035] Figure 1 Flow chart of the method for preparing the composite oxide film provided in this application
[0036] Figure 2 A comparison diagram of the pore sizes of the composite oxide film provided in this application before and after micropore corrosion;
[0037] Figure 3 A cross-sectional comparison diagram of the composite oxide film provided in this application before and after microporous corrosion;
[0038] Figure 4 It is a partial schematic diagram of the composite oxide film after Delam in Example 1, Examples 10 to 13 and Comparative Example 1 of the present application. [Specific implementation method]
[0039] In order to better understand the technical solution of the present application, the embodiments of the present application are described in detail below with reference to the accompanying drawings.
[0040] It should be clear that the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present application.
[0041] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "said" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0042] It should be understood that the term "and / or" used in this article is only a description of the association relationship of associated objects, indicating that there can be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.
[0043] It should be noted that the directional words such as "upper", "lower", "left", and "right" described in the embodiments of the present application are described at the angles shown in the accompanying drawings and should not be understood as limiting the embodiments of the present application. In addition, in the context, it is also necessary to understand that when it is mentioned that an element is connected to another element "upper" or "lower", it can not only be directly connected to another element "upper" or "lower", but also indirectly connected to another element "upper" or "lower" through an intermediate element.
[0044] The present application provides a method for preparing a composite oxide film, and the method for preparing a composite oxide film comprises:
[0045] Anodizing the surface of a metal workpiece to form an oxide layer;
[0046] The modified organic silicon polymer is deposited on the oxide layer by cathode electrophoretic coating technology to form a deposition layer, thereby obtaining a composite oxide film; wherein the modified organic silicon polymer contains a positively charged modified epoxy resin unit and a negatively charged hydrophobic fluorine-containing group.
[0047] The preparation method of the composite oxide film in the above scheme uses cathode electrophoretic painting technology to deposit the modified organic silicon polymer on the oxide layer to form a deposition layer. The deposition layer attached to the oxide layer can provide protection, improve the wear resistance of the oxide layer, and extend the service life of the oxide layer. In addition, the deposition layer contains positively charged modified epoxy resin units. The positive charge can enhance the bonding force between the deposition layer and the oxide layer on the surface of the negatively charged metal workpiece, prevent the deposition layer from falling off during use, and extend the protection time of the deposition layer on the oxide layer; at the same time, the deposition layer also contains negatively charged hydrophobic fluorine-containing groups. The hydrophobicity of the fluorine-containing groups can significantly reduce the interaction between water molecules, acids, alkalis and other corrosive substances and the surface of the deposition layer, so that the metal workpiece can be used in special environments such as acid and alkali, high humidity, and high temperature.
[0048] Please refer to Figure 1 , the preparation method of the composite oxide film of the present application is described below:
[0049] Step S10, performing anodizing treatment on the surface of the metal workpiece to form an oxide layer.
[0050] In step S10, the material of the metal workpiece used in the present application is aluminum or its alloy. The anodizing treatment of aluminum or its alloy specifically includes the steps of pretreatment, preparation of electrolyte, anodizing and post-treatment.
[0051] Pretreatment specifically includes cleaning, polishing or grinding, pickling, etc. Among them, the cleaning process usually uses a cleaning agent to remove grease, dust and other contaminants on the surface of the metal workpiece. The type of cleaning agent can be selected according to the material of the metal workpiece and is not limited here; polishing or grinding can obtain a smoother metal workpiece surface; pickling can remove oxides and impurities on the surface of the metal workpiece and improve the quality of the subsequently prepared oxide layer.
[0052] The type of electrolyte used for anodizing can be selected according to the characteristics of the oxide layer to be formed and the type of metal workpiece. For example, for aluminum or its alloys, sulfuric acid, oxalic acid, chromic acid and other electrolytes can be used, which are not limited here.
[0053] During the anodizing process, the metal workpiece is used as the anode, and an inert material such as platinum or stainless steel is placed in the electrolyte as the cathode. At this time, a direct current is applied through the power supply to cause an oxidation reaction on the metal surface on the anode to form a dense oxide film. The current density, electrolyte temperature, processing time and other parameters are controlled according to the required oxide layer thickness and characteristics.
[0054] The post-treatment process is to use deionized water or other cleaning fluids to clean the surface of the metal workpiece to remove residual electrolyte, thereby obtaining a metal workpiece with a dense oxide layer, which can significantly improve the corrosion resistance, wear resistance and aesthetics of the metal workpiece.
[0055] The oxide layer formed by the anodizing treatment in the present application is an aluminum oxide layer, and the thickness of the aluminum oxide layer is 500nm to 700nm. Optionally, the thickness of the oxide layer can be 500nm, 550nm, 600nm, 650nm and 700nm, etc., or other values within the range, which can be selected according to actual needs and are not limited here. It can be understood that an aluminum oxide layer that is too thick will reduce its toughness and increase its preparation cost, and an aluminum oxide layer that is too thin may not provide sufficient protection, and its corrosion resistance and wear resistance are affected. The thickness of the oxide layer of the present application is within the above range, and an aluminum oxide layer with low cost, long service life, and excellent wear resistance and corrosion resistance can be obtained.
[0056] In some embodiments, after step S10, step S11 is further included: using a corrosive solution to corrode the oxide layer to form diffuse reflective microcracks.
[0057] In step S11, the etching solution contains SO4 2- , SO4 2- The concentration is 0.03mol / L~3mol / L, optional, SO4 2- The concentration of can be 0.03mol / L, 0.1mol / L, 0.15mol / L, 0.2mol / L, 0.25mol / L and 0.3mol / L, etc., or other values within the range, which can be selected according to actual needs and are not limited here. Preferably, the SO4-containing 2- The corrosion solution is Al2(SO4)3, the concentration of Al2(SO4)3 is 0.01mol / L~1mol / L, and the specific reaction process of Al2(SO4)3 and aluminum oxide layer is:
[0058]
[0059] 3H2SO4(dilute)+Al2O3(oxide film)→Al2(SO4)3+3H2O;
[0060] Understandable, see Figure 2 and Figure 3 The oxide layer formed after anodizing is a porous structure. With the action of Al2(SO4)3 corrosive solution, the surface and micropore structure of the oxide layer change, which increases the pore size of the micropores in the oxide layer. Many tiny cracks and depressions are formed on the surface of the oxide layer and the inner wall of the micropores, namely diffuse reflection microcracks. At this time, the cracks and depressions cause the reflection of light on the oxide layer to no longer be a single-direction specular reflection, but to scatter in multiple directions, thereby producing a diffuse reflection effect, making the appearance of the metal workpiece with an oxide layer appear white.
[0061] The reaction temperature of the above-mentioned corrosion treatment is 40℃~70℃, and the reaction time is 2min~8min. Optionally, the reaction temperature can be 40℃, 45℃, 50℃, 55℃, 60℃, 65℃ and 70℃, etc., and the reaction time can be 2min, 3min, 4min, 5min, 6min, 7min and 8min, etc., or other values within the range. It can be selected according to actual needs and is not limited here. It can be understood that the reaction temperature will affect the corrosion rate, and then affect the formation speed and microcrack size of diffuse reflection microcracks. The reaction time will affect the formation number and microcrack size of diffuse reflection microcracks. The reaction time and temperature of the corrosion treatment of this application are within the above range, and diffuse reflection microcracks of moderate size and number can be formed on the oxide layer. The structure of the diffuse reflection microcracks formed by the Al2(SO4)3 corrosion solution is stable and not easily damaged by external forces.
[0062] The width of the diffuse reflection microcracks is 5nm to 20nm, and the depth is 30nm to 50nm. Optionally, the width of the diffuse reflection microcracks can be 5nm, 10nm, 15nm and 20nm, etc., and the depth can be 30nm, 35nm, 40nm, 45nm and 50nm, etc., or other values within the range. It can be selected according to actual needs and is not limited here. It can be understood that the width of the diffuse reflection microcracks will affect the scattering effect of light. Wider microcracks will cause a larger light scattering angle, increase the number of scattering directions, and thus produce a stronger diffuse reflection effect; the depth of the microcracks will affect the length of the propagation path of the light. The longer propagation path increases the chance of light interacting with the surface structure of the metal workpiece, but excessive width and depth will affect the structural integrity of the oxide layer and reduce its service life. The width and depth of the diffuse reflection microcracks of the present application are within the above range. While ensuring the structural integrity of the oxide layer, it can produce a stronger diffuse reflection effect, making the white effect of the metal surface better and the color distribution more uniform.
[0063] Before corrosion, the pore size of the oxide layer is 20nm to 50nm. The pore size of the oxide layer after corrosion is 40nm to 80nm. Optionally, the pore size of the oxide layer after corrosion can be 40nm, 50nm, 60nm, 70nm, 80nm, etc., or other values within the range, which can be selected according to actual needs and are not limited here. It can be understood that the pore size of the oxide layer after corrosion is within the above range, which can ensure that the oxide layer has good compactness, thereby effectively preventing water, acid substances and alkaline substances from penetrating into the metal workpiece.
[0064] Step S20, using cathode electrophoretic coating technology to deposit the modified organic silicon polymer on the oxide layer to form a deposition layer to obtain a composite oxide film; wherein the modified organic silicon polymer contains a positively charged modified epoxy resin unit and a negatively charged hydrophobic fluorine-containing group.
[0065] In step S20, during the treatment process of cathodic electrophoretic painting technology, the metal workpiece with an oxide layer serves as the cathode, and the modified silicone polymer containing a positive charge serves as the anode. When a DC voltage is applied, the positively charged modified silicone polymer moves toward the cathode and is deposited on the surface of the metal workpiece to form a deposition layer.
[0066] Among them, the reaction temperature of cathodic electrophoretic painting technology is 25℃~30℃, the reaction voltage is 60V~70V, and the reaction time is 25s~30s. Optionally, the reaction temperature can be 25℃, 26℃, 27℃, 28℃, 29℃ and 30℃, etc., the voltage can be 60V, 62V, 64V, 66V, 68V and 70V, etc., the reaction time can be 25s, 26s, 27s, 28s, 29s and 30s, etc., or other values within the range. It can be selected according to actual needs and is not limited here. It can be understood that the reaction temperature of the electrophoresis process will affect the viscosity of the modified silicone polymer coating, and then affect the fluidity of the modified silicone polymer coating; the reaction voltage is the power source that drives the deposited particles to move to the metal surface, affecting the movement speed of the coating particles, and thus improving the deposition efficiency; the reaction time will affect the deposition thickness and uniformity of the deposited layer. The reaction temperature, voltage and time of the electrophoresis process of the present application are within the above range, which can accelerate the formation of the deposited layer and ensure the deposition quality of the deposited layer.
[0067] The deposition layer prepared by the cathode electrophoretic coating technology is formed on the surface of the oxide layer, in the pores of the oxide layer and in the diffuse reflection cracks, which can fix the microcracks. The deposition thickness is 5μm to 20μm. Optionally, the deposition thickness of the deposition layer can be 5μm, 10μm, 25μm and 20μm, etc., or other values within the range. It can be selected according to actual needs and is not limited here. It can be understood that the thickness of the deposition layer is within the above range, which plays a role in fixing the microcracks while enhancing the light transmittance of the deposition layer and reducing the influence of the deposition layer on the diffuse reflection effect of the microcracks.
[0068] In some embodiments, before step S20, step S12 is further included: preparing a modified organic silicon polymer, and the preparation of the modified organic silicon polymer includes:
[0069] Firstly, the organosilicon-modified epoxy acrylic resin and an amine ring-opening agent are subjected to a ring-opening reaction to obtain a ring-opening product; and then the ring-opening product is subjected to an acidification treatment to obtain a modified organosilicon high molecular polymer.
[0070] The reaction process of step S12 is:
[0071]
[0072] The amine ring-opening agent includes at least one of monoethanolamine, diethanolamine and triethanolamine, which can be selected according to actual needs and is not limited here.
[0073] The addition ratio of the amine ring-opening agent is 5% to 10%. Optionally, the addition ratio of the amine ring-opening agent can be 5%, 6%, 7%, 8%, 9% and 10%, etc., or other values within the range. It can be selected according to actual needs and is not limited here. It can be understood that the amine compound as a ring-opening agent can react with the epoxy group in the silicone-modified epoxy acrylic resin to generate an intermediate containing more active functional groups; in addition, the amine group has a strong nucleophilic property. In the subsequent deposition process, the amine group can attract H + Ions make the modified silicone polymer carry a positive charge, which helps to promote the modified silicone polymer to move to the cathode, thereby depositing on the metal surface to form a deposition layer. The addition ratio of the amine ring-opening agent is within the above range, which can accelerate the ring-opening process.
[0074] A curing agent is also required in the ring-opening reaction. The curing agent used in the present application can be at least one of o-phenylenediisocyanate, toluene diisocyanate, hexamethyl diisocyanate and ethylene glycol ethyl ether, which can be selected according to actual needs and is not limited here. It can be understood that the curing agent can promote the ring opening of the epoxy group.
[0075] The temperature of the ring-opening reaction is 40°C to 60°C, and the time is 0.5h to 2h. Optionally, the time of the ring-opening reaction can be specifically 40°C, 40°C, 40°C, 40°C, 40°C, 40°C, 40°C and 40°C, etc. The time can be specifically 0.5h, 0.5h, 1.1h, 1.1h, 1.1h and 2h, etc., or other values within the range. It can be selected according to actual needs and is not limited here.
[0076] After the ring-opening reaction, an acidification treatment is performed. The acidification treatment can promote the protonation of the amine group in the intermediate of the active functional group, so that the modified silicone polymer obtained has a positive charge, which helps to promote the modified silicone polymer to move to the cathode during the cathodic electrophoretic painting process, thereby depositing on the metal surface to form a deposition layer.
[0077] In some embodiments, before step S12, step S13 is further included: preparing an organosilicon-modified epoxy acrylic resin, and the preparation of the organosilicon-modified epoxy acrylic resin includes:
[0078] Epoxy resin, hydroxyl chain extender, methacrylamide and modified silicone quantum dots are mixed in a preset mass ratio and then subjected to polymerization reaction to obtain silicone-modified epoxy acrylic resin; wherein the preset mass ratio is (50-100): (2-30): (10-50): (1-10).
[0079] The reaction process of step S13 is:
[0080]
[0081] Among them, epoxy resin is the main component of silicone modified epoxy acrylic resin; hydroxyl chain extender can react with epoxy groups in epoxy resin to introduce new hydroxyl functional groups, which can further react with epoxy groups to form longer chains, thereby increasing the molecular weight of epoxy resin and improving material strength. The hydroxyl chain extender used in this application can be ethylene glycol ethyl ether, dimethylol propionic acid and dimethylol butyric acid, etc.; the addition of modified silicone quantum dots can enhance the white appearance of the composite oxide layer. Methacrylamide and modified silicone quantum dots are the main components of silicone modified epoxy acrylic resin.
[0082] The ratio of epoxy resin, hydroxyl chain extender, methacrylamide and modified silicone quantum dots is (50-100): (2-30): (10-50): (1-10). It can be understood that epoxy resin is the main material, and the amount of hydroxyl chain extender will affect the crosslinking density and molecular weight of the silicone modified epoxy acrylic resin. The ratio of epoxy resin, hydroxyl chain extender, methacrylamide and modified silicone quantum dots is within the above range. The obtained silicone modified epoxy acrylic resin can be used to prepare the strength and hardness of the composite oxide layer.
[0083] Preferably, the amount of modified silicone quantum dots added is 1wt% to 2wt%. It can be understood that the addition of modified silicone quantum dots can improve the transparency of the deposited layer, and as the Si content in the modified silicone quantum dots increases, the Si-O bonds of the prepared composite oxide film increase, and the strength of the composite oxide film increases. However, when the amount of modified silicone quantum dots added is greater than 2wt%, the brittleness of the composite oxide film will increase, affecting its adhesion to the surface of the metal workpiece.
[0084] The above-mentioned polymerization reaction also requires the addition of a polymerization initiator, which can be azobisisobutyronitrile, azobisisoheptanenitrile, dimethyl azobisisobutyrate, etc., and the amount of the polymerization initiator added is 0.1% to 5%. Optionally, the amount of the polymerization initiator added can be 0.1%, 1%, 2%, 3%, 4% and 5%, etc., or other values within the range. It can be selected according to actual needs and is not limited here. It can be understood that the amount of the polymerization initiator added will affect the rate of the polymerization reaction and the molecular weight of the silicone-modified epoxy acrylic resin. For example, too little polymerization initiator will reduce the reaction rate and the molecular weight of the silicone-modified epoxy acrylic resin, while too much polymerization initiator will cause the reaction rate to be too fast and difficult to control. The amount of the polymerization initiator added in this application is within the above range, which can ensure the smooth progress of the polymerization reaction.
[0085] The temperature of the polymerization reaction is 40°C to 85°C, and the time is 2h to 8h. Optionally, the temperature of the polymerization reaction can be 40°C, 50°C, 60°C, 70°C, 80°C and 85°C, etc., and the time can be 2h, 3h, 4h, 5h, 6h, 7h and 8h, etc., or other values within the range. It can be selected according to actual needs and is not limited here. It can be understood that temperature will affect the reaction rate of the polymerization reaction. An increase in temperature can accelerate the reaction rate; a longer reaction time can ensure that more monomers participate in the reaction and form a longer polymer chain; but too high a temperature and too long a time will lead to the occurrence of side reactions. The molecular weight of the organosilicon-modified epoxy acrylic resin prepared at too low a temperature and too short a time does not meet the required requirements. The temperature and time of the polymerization reaction of this application are within the above range, which can ensure that an organosilicon-modified epoxy acrylic resin with excellent performance is obtained and the occurrence of side reactions is reduced.
[0086] In some embodiments, before step S13, step S14 is further included: preparing modified organic silicon quantum dots, and the preparation of modified organic silicon quantum dots includes:
[0087] Hydroxypropyl methacrylate and perfluorooctyltriethoxysilane are mixed in a preset mass ratio and reacted to obtain modified silicone quantum dots; wherein the preset mass ratio is (2-8): (1-3).
[0088] The reaction process of step S14 is:
[0089]
[0090] The mass ratio of hydroxypropyl methacrylate to perfluorooctyl triethoxysilane is (2-8): (1-3). It can be understood that hydroxypropyl methacrylate is used to prepare modified silicone quantum dots, which can be grafted and copolymerized with epoxy resin later; polysiloxane has good hydrophobicity, heat resistance, and biocompatibility, and the perfluoro group in perfluorooctyl triethoxysilane further enhances the hydrophobicity of the composite oxide film. In addition, Si-OC in polysiloxane is stronger than conventional CC, which can further enhance the strength of the composite oxide film. When the ratio of the two is within the above range, the modified silicone quantum dots can be used to prepare composite oxide films with excellent performance.
[0091] During the above reaction process, a catalyst needs to be added. The catalyst used in this application is K2CO3, Na2CO3, NaHCO3, etc., which can be selected according to actual needs and are not limited here.
[0092] The temperature of the catalytic reaction is 30°C to 90°C, and the time is 0.5h to 5h. Optionally, the temperature of the catalytic reaction can be 3.°C, 40°C, 50°C, 60°C, 70°C, 80°C and 90°C, etc., and the time can be 0.5h, 1h, 2h, 3h, 4h, and 5h, etc., or other values within the range. It can be selected according to actual needs and is not limited here. It can be understood that temperature will affect the reaction rate of the catalytic reaction, and an increase in temperature will accelerate the reaction rate; a longer reaction time can ensure that the reaction is more thorough; but too high a temperature and too long a time will lead to side reactions, and too low a temperature and too long a time will lead to incomplete reactions. The temperature and time of the catalytic reaction in this application are within the above range, which can ensure the stable preparation process of the modified silicone quantum dots.
[0093] After step S20, the modified organic silicon polymer having a negatively charged perfluoro group at one end and a positively charged perfluoro group at the other end of the present application can be obtained.
[0094]
[0095] Modified silicone polymer can be used to prepare the composite oxide film of the present application, and the composite oxide film includes an oxide layer and a deposition layer formed on the oxide layer, the deposition layer includes a modified silicone polymer containing positively charged modified epoxy resin units and negatively charged hydrophobic fluorine-containing groups, and the oxide layer contains diffuse reflective microcracks, and the deposition layer is formed on the surface of the oxide layer and in the diffuse reflective cracks.
[0096] The thickness of the composite oxide film is 10 μm to 30 μm. Optionally, the thickness of the composite oxide film can be 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, etc., or other values within the range. It can be selected according to actual needs and is not limited here. It can be understood that the composite oxide film can be ensured to have good compactness, thereby effectively preventing water, acid substances and alkaline substances from penetrating into the metal workpiece.
[0097] The L value of the composite oxide film is ≥90. Optionally, the L value of the composite oxide film can be 90, 91, 92, 93, 94, 95, 96, etc., or other values within the range. It can be selected according to actual needs and is not limited here. It can be understood that the L value of the composite oxide film refers to the brightness value of the oxide film in the CIE Lab color space. The L value indicates the lightness of the color. The higher the L value, the closer the color is to white or brighter. The L value of the composite oxide film of the present application is ≥90, that is, the composite oxide film has a white appearance.
[0098] The water contact angle of the composite oxide film is ≥130°. Optionally, the water contact angle of the composite oxide film can be 130°, 131°, 132°, 133°, 134°, 135°, etc., or other values within the range, which can be selected according to actual needs and are not limited here. It can be understood that a water contact angle of ≥130° indicates that the composite oxide film has super hydrophobicity, which can significantly reduce the interaction between water molecules, acids, alkalis and other corrosive substances and the surface of the deposited layer, so that the metal workpiece can be used in special environments such as acid and alkali, high humidity, and high temperature.
[0099] The technical solution of the present application is described below in conjunction with specific embodiments:
[0100] Example 1
[0101] (1) An aluminum substrate is anodized to form an aluminum oxide layer, and an Al2(SO4)3·18H2O solution is used to etch the aluminum oxide layer to form diffuse reflective microcracks; wherein the concentration of the Al2(SO4)3·18H2O solution is 0.02 mol / L, the corrosion reaction temperature is 55°C, and the time is 7 min;
[0102] (2) epoxy resin, ethylene glycol ethyl ether, methacrylamide, modified organosilicon quantum dots and azobisisobutyronitrile are mixed in a ratio of 66:14:18:2, the mixture is polymerized to form organosilicon-modified epoxy acrylic resin, the organosilicon-modified epoxy acrylic resin is subjected to a ring-opening reaction with monoethanolamine and acidified to obtain a modified organosilicon polymer; wherein the mass fraction of the modified organosilicon quantum dots is 2 wt %;
[0103] (3) The modified organic silicon polymer is deposited on the aluminum oxide layer by cathode electrophoretic coating technology to form a deposition layer to obtain a composite oxide film; wherein the temperature of the electrophoretic process is 30° C., the voltage is 60 V, and the time is 30 s.
[0104] Example 2
[0105] (1) An aluminum substrate is anodized to form an aluminum oxide layer, and an Al2(SO4)3·18H2O solution is used to etch the aluminum oxide layer to form diffuse reflective microcracks; wherein the concentration of the Al2(SO4)3·18H2O solution is 0.05 mol / L, the corrosion reaction temperature is 55°C, and the time is 7 min;
[0106] (2) epoxy resin, ethylene glycol ethyl ether, methacrylamide, modified organosilicon quantum dots and azobisisobutyronitrile are mixed in a ratio of 66:14:18:2, the mixture is polymerized to form organosilicon-modified epoxy acrylic resin, the organosilicon-modified epoxy acrylic resin is subjected to a ring-opening reaction with monoethanolamine and acidified to obtain a modified organosilicon polymer; wherein the mass fraction of the modified organosilicon quantum dots is 2 wt %;
[0107] (3) The modified organic silicon polymer is deposited on the aluminum oxide layer by cathode electrophoretic coating technology to form a deposition layer to obtain a composite oxide film; wherein the temperature of the electrophoretic process is 60° C., the voltage is 60 V, and the time is 30 s.
[0108] Example 3
[0109] (1) An aluminum substrate is anodized to form an aluminum oxide layer, and an Al2(SO4)3·18H2O solution is used to etch the aluminum oxide layer to form diffuse reflective microcracks; wherein the concentration of the Al2(SO4)3·18H2O solution is 0.1 mol / L, the corrosion reaction temperature is 55°C, and the time is 7 min;
[0110] (2) epoxy resin, ethylene glycol ethyl ether, methacrylamide, modified organosilicon quantum dots and azobisisobutyronitrile are mixed in a ratio of 66:14:18:2, the mixture is polymerized to form organosilicon-modified epoxy acrylic resin, the organosilicon-modified epoxy acrylic resin is subjected to a ring-opening reaction with monoethanolamine and acidified to obtain a modified organosilicon polymer; wherein the mass fraction of the modified organosilicon quantum dots is 2 wt %;
[0111] (3) The modified organic silicon polymer is deposited on the aluminum oxide layer by cathode electrophoretic coating technology to form a deposition layer to obtain a composite oxide film; wherein the temperature of the electrophoretic process is 80° C., the voltage is 60 V, and the time is 30 s.
[0112] Example 4
[0113] (1) An aluminum substrate is anodized to form an aluminum oxide layer, and an Al2(SO4)3·18H2O solution is used to etch the aluminum oxide layer to form diffuse reflective microcracks; wherein the concentration of the Al2(SO4)3·18H2O solution is 0.05 mol / L, the corrosion reaction temperature is 40°C, and the time is 5 min;
[0114] (2) epoxy resin, ethylene glycol ethyl ether, methacrylamide, modified organosilicon quantum dots and azobisisobutyronitrile are mixed in a ratio of 66:14:18:2, the mixture is polymerized to form organosilicon-modified epoxy acrylic resin, the organosilicon-modified epoxy acrylic resin is subjected to a ring-opening reaction with monoethanolamine and acidified to obtain a modified organosilicon polymer; wherein the mass fraction of the modified organosilicon quantum dots is 2 wt %;
[0115] (3) The modified organic silicon polymer is deposited on the aluminum oxide layer by cathode electrophoretic coating technology to form a deposition layer to obtain a composite oxide film; wherein the temperature of the electrophoretic process is 25° C., the voltage is 10 V, and the time is 25 s.
[0116] Example 5
[0117] (1) An aluminum substrate is anodized to form an aluminum oxide layer, and an Al2(SO4)3·18H2O solution is used to etch the aluminum oxide layer to form diffuse reflective microcracks; wherein the concentration of the Al2(SO4)3·18H2O solution is 0.05 mol / L, the corrosion reaction temperature is 60°C, and the time is 5 min;
[0118] (2) epoxy resin, ethylene glycol ethyl ether, methacrylamide, modified organosilicon quantum dots and azobisisobutyronitrile are polymerized to form organosilicon-modified epoxy acrylic resin, and the organosilicon-modified epoxy acrylic resin is subjected to a ring-opening reaction with monoethanolamine and acidified to obtain a modified organosilicon polymer; wherein the mass fraction of the modified organosilicon quantum dots is 2 wt %;
[0119] (3) The modified organic silicon polymer is deposited on the aluminum oxide layer by cathode electrophoretic coating technology to form a deposition layer to obtain a composite oxide film; wherein the temperature of the electrophoretic process is 25° C., the voltage is 70 V, and the time is 25 s.
[0120] Example 6
[0121] (1) An aluminum substrate is anodized to form an aluminum oxide layer, and an Al2(SO4)3·18H2O solution is used to etch the aluminum oxide layer to form diffuse reflective microcracks; wherein the concentration of the Al2(SO4)3·18H2O solution is 0.05 mol / L, the corrosion reaction temperature is 80°C, and the time is 5 min;
[0122] (2) epoxy resin, ethylene glycol ethyl ether, methacrylamide, modified organosilicon quantum dots and azobisisobutyronitrile are mixed in a ratio of 66:14:18:2, the mixture is polymerized to form organosilicon-modified epoxy acrylic resin, the organosilicon-modified epoxy acrylic resin is subjected to a ring-opening reaction with monoethanolamine and acidified to obtain a modified organosilicon polymer; wherein the mass fraction of the modified organosilicon quantum dots is 2 wt %;
[0123] (3) The modified organic silicon polymer is deposited on the aluminum oxide layer by cathode electrophoretic coating technology to form a deposition layer to obtain a composite oxide film; wherein the temperature of the electrophoretic process is 25° C., the voltage is 100 V, and the time is 25 s.
[0124] Example 7
[0125] (1) An aluminum substrate is anodized to form an aluminum oxide layer, and an Al2(SO4)3·18H2O solution is used to etch the aluminum oxide layer to form diffuse reflective microcracks; wherein the concentration of the Al2(SO4)3·18H2O solution is 0.04 mol / L, the corrosion reaction temperature is 50°C, and the time is 2 min;
[0126] (2) epoxy resin, ethylene glycol ethyl ether, methacrylamide, modified organosilicon quantum dots and azobisisobutyronitrile are mixed in a ratio of 66:14:18:2, the mixture is polymerized to form organosilicon-modified epoxy acrylic resin, the organosilicon-modified epoxy acrylic resin is subjected to a ring-opening reaction with monoethanolamine and acidified to obtain a modified organosilicon polymer; wherein the mass fraction of the modified organosilicon quantum dots is 2 wt %;
[0127] (3) The modified organic silicon polymer is deposited on the aluminum oxide layer by cathode electrophoretic coating technology to form a deposition layer to obtain a composite oxide film; wherein the temperature of the electrophoretic process is 40° C., the voltage is 55 V, and the time is 10 s.
[0128] Example 8
[0129] (1) An aluminum substrate is anodized to form an aluminum oxide layer, and an Al2(SO4)3·18H2O solution is used to etch the aluminum oxide layer to form diffuse reflective microcracks; wherein the concentration of the Al2(SO4)3·18H2O solution is 0.04 mol / L, the corrosion reaction temperature is 50°C, and the time is 6 min;
[0130] (2) epoxy resin, ethylene glycol ethyl ether, methacrylamide, modified organosilicon quantum dots and azobisisobutyronitrile are mixed in a ratio of 66:14:18:2, the mixture is polymerized to form organosilicon-modified epoxy acrylic resin, the organosilicon-modified epoxy acrylic resin is subjected to a ring-opening reaction with monoethanolamine and acidified to obtain a modified organosilicon polymer; wherein the mass fraction of the modified organosilicon quantum dots is 2 wt %;
[0131] (3) The modified organic silicon polymer is deposited on the aluminum oxide layer by cathode electrophoretic coating technology to form a deposition layer to obtain a composite oxide film; wherein the temperature of the electrophoretic process is 40° C., the voltage is 55 V, and the time is 60 s.
[0132] Example 9
[0133] (1) An aluminum substrate is anodized to form an aluminum oxide layer, and an Al2(SO4)3·18H2O solution is used to etch the aluminum oxide layer to form diffuse reflective microcracks; wherein the concentration of the Al2(SO4)3·18H2O solution is 0.04 mol / L, the corrosion reaction temperature is 50°C, and the time is 10 min;
[0134] (2) epoxy resin, ethylene glycol ethyl ether, methacrylamide, modified organosilicon quantum dots and azobisisobutyronitrile are mixed in a ratio of 66:14:18:2, the mixture is polymerized to form organosilicon-modified epoxy acrylic resin, the organosilicon-modified epoxy acrylic resin is subjected to a ring-opening reaction with monoethanolamine and acidified to obtain a modified organosilicon polymer; wherein the mass fraction of the modified organosilicon quantum dots is 2 wt %;
[0135] (3) The modified organic silicon polymer is deposited on the aluminum oxide layer by cathode electrophoretic coating technology to form a deposition layer to obtain a composite oxide film; wherein the temperature of the electrophoretic process is 40° C., the voltage is 55 V, and the time is 120 s.
[0136] Example 10
[0137] The difference from Example 1 is that epoxy resin, ethylene glycol ethyl ether, methacrylamide, modified silicone quantum dots and azobisisobutyronitrile are mixed in a ratio of 100:30:50:1, the mixture is polymerized to form silicone-modified epoxy acrylic resin, the silicone-modified epoxy acrylic resin is subjected to a ring-opening reaction with monoethanolamine and acidified to obtain a modified silicone polymer; wherein the mass fraction of the modified silicone quantum dots is 0.5wt%.
[0138] Embodiment 11
[0139] The difference from Example 1 is that epoxy resin, ethylene glycol ethyl ether, methacrylamide, modified silicone quantum dots and azobisisobutyronitrile are mixed in a ratio of 100:30:50:1.82, the mixture is polymerized to form silicone-modified epoxy acrylic resin, the silicone-modified epoxy acrylic resin is subjected to a ring-opening reaction with monoethanolamine and acidified to obtain a modified silicone polymer; wherein the mass fraction of the modified silicone quantum dots is 1wt%.
[0140] Example 12
[0141] The difference from Example 1 is that epoxy resin, ethylene glycol ethyl ether, methacrylamide, modified silicone quantum dots and azobisisobutyronitrile are mixed in a ratio of 100:30:50:2.74, the mixture is polymerized to form silicone-modified epoxy acrylic resin, the silicone-modified epoxy acrylic resin is subjected to a ring-opening reaction with monoethanolamine and acidified to obtain a modified silicone polymer; wherein the mass fraction of the modified silicone quantum dots is 1.5wt%.
[0142] Embodiment 13
[0143] The difference from Example 1 is that epoxy resin, ethylene glycol ethyl ether, methacrylamide, modified silicone quantum dots and azobisisobutyronitrile are mixed in a ratio of 100:30:50:4.62, the mixture is polymerized to form silicone-modified epoxy acrylic resin, the silicone-modified epoxy acrylic resin is subjected to a ring-opening reaction with monoethanolamine and acidified to obtain a modified silicone polymer; wherein the mass fraction of the modified silicone quantum dots is 2.5wt%.
[0144] Comparative Example 1
[0145] Different from Example 1, no modified organic silicon quantum dots are added.
[0146] The composite oxide films obtained in Examples 1 to 13 and Comparative Example 1 were cured at a temperature of 100° C. to 200° C. for 0.5 h to 3 h, and tested:
[0147] (1) Test the pore size of the composite oxide films of Examples 1 to 9:
[0148] (2) Observation of the appearance of the composite oxide films of Examples 1 to 9:
[0149] (3) Using a colorimeter to measure the L / a / b values of the composite oxide films of Example 1, Examples 10 to 13 and Comparative Example 1;
[0150] (4) Using a microhardness tester to test the Delam values of the composite oxide films of Example 1, Examples 10 to 13 and Comparative Example 1;
[0151] (5) The WCA values of the composite oxide films of Example 1, Examples 10 to 13 and Comparative Example 1 were tested using a water drop angle tester.
[0152] Test results:
[0153] Table 1
[0154]
[0155]
[0156] Table 2
[0157]
[0158] Table 3
[0159]
[0160] Test result analysis:
[0161] It can be seen from the test results in Table 1 that in the process of diffuse reflection microcrack formation, the reaction temperature will affect the corrosion rate, and then affect the speed and size of microcrack formation, and the reaction time will affect the number and size of microcrack formation. If the reaction temperature is too high or the reaction time is too long, after the microcracks are formed, the pore size of the oxide layer is too large, affecting its protective effect. The reaction temperature of the present application is within the range of 40°C to 70°C and the reaction time is within the range of 2min to 8min, and a microcrack oxide layer with a moderate pore size can be obtained to ensure its structural stability.
[0162] It can be seen from the test results in Table 2 that during the cathodic electrophoretic painting process, the reaction temperature of the electrophoretic process will affect the viscosity of the modified silicone polymer coating, and then affect the fluidity of the modified silicone polymer coating; the reaction voltage is the power source that drives the deposited particles to move to the metal surface, affecting the movement speed of the coating particles, and then improving the deposition efficiency; the reaction time will affect the deposition thickness and uniformity of the deposited layer; if the temperature and voltage of the electrophoretic process are too high or the time is too long, the deposited layer will solidify too quickly, the internal structure of the film will be uneven, the bubbles cannot be discharged in time, and the surface roughness may cause cracks, and then the transparency of the deposited layer will deteriorate, affecting the appearance color of the metal workpiece; if the temperature and voltage of the electrophoretic process are too low or the time is too short, the thickness of the deposited layer is too thin. The temperature of the electrophoretic process of the present application is within the range of 25°C to 30°C, the voltage is 60V to 70V, and the time is within the range of 25s to 30s, and a deposited layer with a qualified appearance can be obtained.
[0163] From the test results in Table 3, it can be seen that the addition of modified silicone quantum dots can improve the transparency of the deposited layer. When the addition amount of modified silicone quantum dots is 1wt% to 2wt%, the L value is greater than 90, and the appearance of the composite oxide film is white; as the amount of modified silicone quantum dots increases, the Si content increases, the Si-O bonds of the composite oxide film increase, the strength of the composite oxide film increases, and the bonding force between the deposited layer and the oxide layer is strong. However, when the amount of modified silicone quantum dots is greater than 2.5wt%, the film becomes more brittle and the adhesion decreases; at the same time, the surface hydrophobicity of the composite oxide film is positively correlated with the content of perfluorinated groups. As the addition amount of modified silicone quantum dots increases, the hydrophobic fluorine-containing groups increase, and the hydrophobicity of the composite oxide film is enhanced.
[0164] Please refer to Figure 4 In Examples 1, 11 and 12, the mass fraction of the modified silicone quantum dots is between 0.5wt% and 2wt%, the strength of the composite oxide film is high, and there is basically no damaged area on the surface of the composite oxide film after the Delam test; in Example 10, the amount of modified silicone quantum dots added is too low, and in Example 13, the amount of modified silicone quantum dots added is too high. In Comparative Example 1, no modified silicone quantum dots are added, which will affect the strength of the composite oxide film, and the surface of the composite oxide film after the Delam test is damaged.
[0165] The above describes in detail the structure, features and effects of the present invention based on the embodiments shown in the drawings. The above is only a preferred embodiment of the present invention, but the present invention is not limited to the scope of implementation shown in the drawings. Any changes made according to the concept of the present invention, or modifications to equivalent embodiments with equivalent changes, which still do not exceed the spirit covered by the description and drawings, should be within the protection scope of the present invention.
Claims
1. A method for preparing a composite oxide film, characterized in that: The method for preparing the composite oxide film comprises the steps of: Anodizing the surface of a metal workpiece to form an oxide layer; The modified organic silicon polymer is deposited on the oxide layer by cathode electrophoretic coating technology to form a deposition layer, thereby obtaining a composite oxide film; wherein the modified organic silicon polymer contains a positively charged modified epoxy resin unit and a negatively charged hydrophobic fluorine-containing group.
2. The method for preparing the composite oxide film according to claim 1, characterized in that: The method also includes preparing the modified organic silicon polymer, wherein the preparation of the modified organic silicon polymer includes: The organosilicon-modified epoxy acrylic resin is subjected to a ring-opening reaction with an amine ring-opening agent to obtain a ring-opening product; wherein the amine ring-opening agent comprises at least one of monoethanolamine, diethanolamine and triethanolamine; The ring-opening product is subjected to acidification treatment to obtain the modified organic silicon high molecular polymer.
3. The method for preparing the composite oxide film according to claim 2, characterized in that: The method also includes preparing the organosilicon-modified epoxy acrylic resin, wherein the preparation of the organosilicon-modified epoxy acrylic resin includes: The epoxy resin, hydroxyl chain extender, methacrylamide and modified silicone quantum dots are mixed in a preset mass ratio and then subjected to polymerization reaction to obtain the silicone-modified epoxy acrylic resin; wherein the preset mass ratio is (50-100): (2-30): (10-50): (1-10).
4. The method for preparing the composite oxide film according to claim 3, characterized in that: The hydroxy chain extender includes at least one of ethylene glycol ethyl ether, dimethylol propionic acid and dimethylol butyric acid.
5. The method for preparing the composite oxide film according to claim 2, characterized in that: The method further includes preparing the modified organic silicon quantum dots, wherein the preparation of the organic silicon quantum dots includes: Hydroxypropyl methacrylate and perfluorooctyltriethoxysilane are mixed in a preset mass ratio and reacted to obtain modified silicone quantum dots; wherein the preset mass ratio is (2-8): (1-3).
6. The method for preparing the composite oxide film according to claim 1, characterized in that: After the surface of the metal workpiece is anodized to form an oxide layer, it also includes: The oxide layer is etched with an etchant solution to form diffuse reflective microcracks.
7. The method for preparing the composite oxide film according to claim 6, characterized in that: The etching solution contains SO4 2- , the SO4 2- The concentration is 0.03mol / L~3mol / L.
8. The method for preparing the composite oxide film according to claim 6, characterized in that: The modified organic silicon polymer is deposited on the oxide layer by using cathodic electrophoretic coating technology to form a deposited layer having at least one of the following characteristics: (1) The reaction temperature is 25°C to 30°C; (2) Voltage is 60V to 70V; (3) The reaction time is 25s to 30s.
9. A composite oxide film, characterized in that: The composite oxide film comprises an oxide layer and a deposition layer formed on the oxide layer, wherein the deposition layer comprises a modified organic silicon macromolecular polymer containing a positively charged modified epoxy resin unit and a negatively charged hydrophobic fluorine-containing group.
10. The composite oxide film according to claim 9, characterized in that: The oxide layer contains diffuse reflective micro cracks, and the deposition layer is formed on the surface of the oxide layer and in the diffuse reflective cracks.
11. The composite oxide film according to claim 10, characterized in that: The composite oxide film has at least one of the following characteristics: (1) The thickness of the composite oxide film is 10 μm to 30 μm; (2) The pore size of the composite oxide film is 40 nm to 80 nm; (3) The width of the diffuse reflection microcracks is 5 nm to 20 nm; (4) The depth of the diffuse reflection microcracks is 30nm to 50nm; (5) The thickness of the deposited layer is 5 μm to 20 μm; (6) The L value of the composite oxide film is ≥90; (7) The water contact angle of the composite oxide film is ≥130°.